Improved Mechanical Properties of Al-Si Alloys by Adding an Extrusion Process to Conventional Processing Method - Han J.Y.; Femi O.E.; Kilicaslan F.; Jeong C.U.; Baeg C.H.; Hong S.J.; Koo J.M. (Walter de Gruyter GmbH, 2017)
AbstractIn this study, the mechanical properties of Al-Si alloys was improved by selecting higher Si content and avoiding distortion in Al-Si matrix by adding an extrusion process such that the fabrication processes casting and extrusion were in sequence. Cast billets were extruded at ratios 4:1 and 10:1 to obtained two extruded bars with different processing parameters. The as-extruded samples were characterized and investigated for microstructure and mechanical properties. Optical Microscope was used to examined phase morphologies and microstructures of the extruded Al-Si bars. Mechanical properties were conducted on each sample to study the effectiveness of the additional extrusion process in high Si content Al-Si alloys. The result shows that by increasing the extrusion ratio, the size of the primary Si particle reduces leading to a higher density, better tensile and yield strength compared to the cast billet.
Keywords: extrusion; Mining engineering. Metallurgy; Al-Si alloys; TN1-997; TA401-492; mechanical properties; Materials of engineering and construction. Mechanics of materials